Role of multiple- and single-pregnancy complications with incident cardiovascular diseases: a nationwide data linkage study in Wales. (3rd October 2022) - Al Bahhawi, T; L Harrison, S; A Lane, D; Buchan, I; Skjoth, F; Sharp, A; Abbasizanjani, H; Akbari, A; Torabi, F; Halcox, J; Lip, G Y H
Abstract: Background: Prior evidence has suggested that pregnancy complications are associated with a higher risk of cardiovascular disease in women. However, associations between coexisting multiple pregnancy complications and incident cardiovascular disease remains unclear. Purpose: To examine the risk of ischemic heart disease (IHD), stroke, atrial fibrillation or heart failure among women after their first pregnancy with a history of multiple pregnancy complications and women with a history of single-pregnancy complications, compared to women without pregnancy complications. Methods: This retrospective cohort included women aged 16–45 years who had their first pregnancy between 2000 and 2018 in Wales using the Secure Anonymised Information Linkage (SAIL) Databank. Data were extracted from various sources such as Office for National Statistics (ONS) birth and death extracts, hospital admission, outpatient, emergency department and General Practice data sources, and pregnancy related data such as maternal indicators and national community child health. Cox proportional hazard regression was used to evaluate the association between multiple or specific single pregnancy complications and incidence of cardiovascular disease. Results: A total of 298, 515 women were included in the study, of which 64, 794 (21.7%) women experienced a single pregnancy complication, and 10, 038 (3.38%) women experienced more than one complication during their first pregnancy. During the a median of 9.7 years of follow-up, 2, 484 women developed incident cardiovascular disease. IHD had the highest incidence rate among women with multiple pregnancy complications at 9.06 (7.36–11.15) per 10, 000 person-years, compared to 4.24 (3.77–4.78) among women with a single pregnancy complication and 2.40 (2.20–2.61) among women without any pregnancy complications. After adjusting for potential confounding factors, compared to no previous pregnancy complications, a history of multiple pregnancy complications was associated with a higher risk of heart failure [hazard ratio (HR) 3.18 (95% confidence interval (CI) 2.34–4.32)], IHD [HR 2.88 (95% CI 2.27–3.67)], stroke [HR 2.03 (95% CI 1.55–2.65)] and atrial fibrillation [HR 1.80 (95% CI 1.20–2.72)]. There was also a consistent trend for a higher risk of all outcomes in women with a history of single-pregnancy complications compared to women without complications during the first pregnancy (Figure 1). Conclusion: This population-scale study used anonymised individual-level linked data from multiple routinely collected data sources. In almost 300, 000 women with a previous pregnancy, multiple pregnancy complications were associated with a higher risk of incident cardiovascular disease, including heart failure, ischaemic heart disease, stroke and atrial fibrillation. Women who experience multiple pregnancy complications may benefit from targeted intervention strategies to reduce their risk of incident cardiovascular disease. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Saudi Arabia governmental PhD studentship